2001
DOI: 10.1080/00365540110076714
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Effects of Linezolid versus Amoxicillin/Clavulanic Acid on the Normal Intestinal Microflora

Abstract: Twelve healthy subjects (6 females, 6 males; age range 18-40 y) participated in this trial. Linezolid was given as 600 mg tablets b.i.d. for 7 d and amoxicillin/clavulanic acid as 1000 mg tablets o.d. for 7 d. The washout period between the administration of the 2 antibacterial agents was 4 weeks. Faecal samples were collected prior to administration (Days -2 and -1), during administration (Days 4 and 8) and after administration (Days 14, 21 and 35) for microbiological analyses. The samples were diluted in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…Similar findings were previously reported, however, for healthy volunteers and only for intestinal enterococci (10). This reduction in colonization could be due to the antibiotics coadministered with linezolid.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar findings were previously reported, however, for healthy volunteers and only for intestinal enterococci (10). This reduction in colonization could be due to the antibiotics coadministered with linezolid.…”
Section: Discussionsupporting
confidence: 79%
“…After 7 days, linezolid suppressed enterococci in the volunteers' intestinal microbiotas. Simultaneously, linezolid decreased the concentration of bifidobacteria, lactobacilli, clostridia, and Bacteroides (10). In mice, linezolid promoted the colonization of Klebsiella pneumoniae with extended-spectrum ␤-lactamase (11).…”
mentioning
confidence: 96%
“…However, information about the pathogenesis of Parabacteroides in patients is still lacking. An approximate return to pretreatment conditions also occurred in this study within days after cessation of treatments, as described by others using different antibiotics [7, 15]. The proportion of Lactobacillus increased while those of Parabacteroides decreased days after cessation of the treatments (Fig.…”
supporting
confidence: 86%
“…The impact of tedizolid on normal intestinal flora was previously shown to be limited and reversible, with no signs of microbiological substitution after 7 days of i.v. or oral administration in healthy subjects (32), while another study showed linezolid to result in marked alterations in gut flora composition (33). In addition, the lower dosing frequency of tedizolid (once daily versus twice daily with linezolid) may also somewhat reduce the risk of developing GI AEs overall.…”
Section: Discussionmentioning
confidence: 99%